INTERNATIONAL LEGAL COOPERATION AND THE PRINCIPLE OF RECIPROCITY: LESSONS FROM EXTRADITION LAW - DOI 10.5935/2448-0517.20200028 - Portalés, Leticia Fontestad (Juris Poiesis - Qualis A3, 2020)
In this work, after making a brief reference to the principle of reciprocity in general, we will refer to its application in the field of international criminal legal cooperation, specifically, its application in the extradition process. However, given that within the European Union this extradition procedure has been replaced by the European arrest warrant ("EAW"), we will end our analysis with a brief reflection on the incidence of this principle in a judicial area such as the European that is governed by the principle of mutual judicial recognition.